When the world runs dry : Earth's water in crisis - Castaldo, Nancy F. (Nancy Fusco), 1962- (Algonquin Young Readers, 2022)
"A narrative nonfiction account of the worldwide water crisis, explaining what's happening to the world's water supply, from industrial pollution to harmful algal blooms, and what kids can do about it"--